2009
DOI: 10.1136/jcp.2009.065615
|View full text |Cite
|
Sign up to set email alerts
|

Use of an elastic stain to show venous invasion in colorectal carcinoma: a simple technique for detection of an important prognostic factor

Abstract: Pathologists should look for morphological clues of VI in H&E stained sections; when VI is not apparent, an elastic tissue stain on all tumour blocks significantly improves identification of VI. Morphological clues include the "unaccompanied artery" and "protruding tongue" signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 22 publications
1
54
0
Order By: Relevance
“…The identification of either sign should trigger the use of an elastin stain to confirm the presence of elastic fibers within the adventitia of the residual vein wall. In a recent study, the application of an elastin stain confirmed the presence of VI in 76% of cases originally deemed equivocal on H&E-stained sections [35]. Other features, such as radiation-induced destruction of veins, or their invasion by tumor beyond all morphologic recognition, may contribute to the significant false-negative rate that has been estimated at 10% to 30% [17,23,38].…”
Section: The Evidence For Special Stainsmentioning
confidence: 93%
See 1 more Smart Citation
“…The identification of either sign should trigger the use of an elastin stain to confirm the presence of elastic fibers within the adventitia of the residual vein wall. In a recent study, the application of an elastin stain confirmed the presence of VI in 76% of cases originally deemed equivocal on H&E-stained sections [35]. Other features, such as radiation-induced destruction of veins, or their invasion by tumor beyond all morphologic recognition, may contribute to the significant false-negative rate that has been estimated at 10% to 30% [17,23,38].…”
Section: The Evidence For Special Stainsmentioning
confidence: 93%
“…The CAP protocol does not provide specific recommendations regarding the processing of colorectal specimens [16], although the RCPath state that a minimum of 4 blocks of the tumor should be taken to optimize the detection of key prognostic features, including EMVI [33]. The impact of the number of tissue blocks on the detection of VI has never formally been addressed, although it is interesting to note that in studies where a greater mean number of blocks was taken, higher rates of VI on standard H&E stains were reported (Table 2) [10,20,25,35,36]. A combinatorial analysis of the blocks examined for each case in the series of Talbot et al [25] showed that 3.9% of cases with EMVI would be missed by routinely examining 5 blocks, rising to 41.3% of cases if only 2 blocks were examined.…”
Section: Specimen-processing Techniquesmentioning
confidence: 96%
“…Tips for identifying it include looking carefully where arteries lie close to tumour, as an artery without an accompanying vein may be due to its replacement by tumour, and also by looking at where the vasculature emerges from its passage through the muscularis propria into the perimesorectal or perimesocolic fat. It has been suggested that modifying the haematoxylin and eosin stain to incorporate elastic fibres [32,33] increases the frequency of identification of extramural vascular invasion. …”
Section: Microscopic Featuresmentioning
confidence: 99%
“…This definition is used to identify venous involvement on H&E-stained slides, but does not help in identifying all instances of VI. Other signs have been implemented as markers of VI on H&E-stained slides, and these include the "protruding tongue" (smooth-bordered protrusion of tumour tissue into pericolorectal fat usually adjacent to an artery) and the "orphan artery" (a focus of circumscribed tumour with an adjoining artery, but no accompanying vein) signs [11,39].…”
Section: The Study Of Utility Of Orcein Staining To Detect VI In Cutamentioning
confidence: 99%
“…Metastases in more than one organ/site or the peritoneum Elastica stainings are reported to be useful in the evaluation of VI in colorectal [7][8][9][10][11][12], gastric [13,14] and oesophageal cancers [15]. The use of elastica stains can provide a more precise identification of VI in CRC compared to routine haematoxylin and eosin (H&E) stain.…”
Section: Introductionmentioning
confidence: 99%